Pengembangan E-LKPD Berbasis SETS-PjBL (Science, Environment, Technology, and Society-Project Based Learning) dalam Pembelajaran IPA untuk Meningkatkan Creative Thinking Siswa SMP - Delfi Vidia Almira (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jember, 2025)
This study aims to develop and analyze the effectiveness of electronic student worksheets (E-LKPD) based on the Science, Environment, Technology, and Society–Project Based Learning (SETS-PjBL) model in enhancing the creative thinking skills of junior high school students on the topic of heat transfer. The research employs a Research and Development (R&D) methodology utilizing the ADDIE development model, which encompasses the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consist of students from class VII G at MTs Negeri 2 Jember. The instruments used include expert validation sheets, pretest-posttest assessments, and student response questionnaires. The results indicate that the developed E-LKPD possesses a high level of validity, with an average expert validation score of 87.5%. Field trials demonstrate an improvement in creative thinking scores by 32.4% following the implementation of the E-LKPD compared to prior usage. Additionally, 92% of students responded positively to the learning process utilizing the E-LKPD. Therefore, the SETS-PjBL-based E-LKPD is effective in enhancing students' creative thinking skills in science education. This study aims to develop and analyze the effectiveness of electronic student worksheets (E-LKPD) based on the Science, Environment, Technology, and Society–Project Based Learning (SETS-PjBL) model in enhancing the creative thinking skills of junior high school students on the topic of heat transfer. The research employs a Research and Development (R&D) methodology utilizing the ADDIE development model, which encompasses the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consist of students from class VII G at MTs Negeri 2 Jember. The instruments used include expert validation sheets, pretest-posttest assessments, and student response questionnaires. The results indicate that the developed E-LKPD possesses a high level of validity, with an average expert validation score of 87.5%. Field trials demonstrate an improvement in creative thinking scores by 32.4% following the implementation of the E-LKPD compared to prior usage. Additionally, 92% of students responded positively to the learning process utilizing the E-LKPD. Therefore, the SETS-PjBL-based E-LKPD is effective in enhancing students' creative thinking skills in science education.
Reuploud file repositori 8 Apr 2026_Firli_tata
Keywords: Creative Thinking; E-LKPD; Science Learning; ETS-PjBL